David Harvey´s Moral Geography (Global Journal of Human-Social Science, 2023)
This article presents some David Harvey s ideas 1980 1998 2005 2006 2011 2013a 2014 2016 2018a 2018b with the aim of demonstrating how the author adresses the issue of justice in Geography reveals the specific problems underlying the topic and how he seeks to solve them The new here dedicates to a cut and an emphasis of the author s own ideas as well as the elaboration of a worldview framework and a view of justice and Injustice in order to think a moral and ethical Geography identifying the problem critic the values the vices and virtues the possible strategies and solution proposed by the Geographer Therefore the text suggests encouraging the reader to possess an inteligibility to recognize in the moral debate through the concept of justice valuable aspects of our research field for the construction of a moral and ethical geographical thought
Keywords: moral geography; geographical thought; justice; vices and virtues